ANALISIS PUTUSAN HAKIM TERHADAP TINDAK PIDANA MEMBERI KESEMPATAN PADA ORANG LAIN UNTUK MENGANGKUT MENJUAL BATU BARA - Yunanda, Shopi; B, Erlina; Baharudin (IBLAM LAW REVIEW, 2021)
The company must have a Mining Business Permit,a Special Mining Business Permit (IUPK),and Business Permit to Transport and Sell Coal.One of the decisions regarding the criminal act of abusing mining business permits is in the decision Number:550/Pid.B/LH/2020/PN.Tjk.The problems in this study are what are the factors causing and how judges consider criminal acts to provide opportunities for other people to use Mining Business Permits (IUP),IUPK and Business Permits to transport and sell coal.Decision Study Number:550/Pid.B/LH /2020/PN.Tjk).This study using secondary data sources and primary data.Factors causing the crime to provide opportunities for other people to use IUP,IUPK,and Business Permits to transport and sell coal were carried out by the Defendant because the Defendant was a worker who was ordered by his superior named Limanto to submit documents on behalf of PT.Prisma Jaya to the truck driver for transport and deliver coal.The judge's consideration of criminal act provides an opportunity for other people to use the IUP,IUPK and business permits to transport and sell coal where the Judge gives a verdict that the defendant is subject to imprisonment for 10 months and the Defendant remains detained and determines that the Defendant is burdened with paying court fees in amount of Rp.5,000.00